Metacognitive strategies, academic motivation and academic performance in entering health science students in a university in Lima - Thornberry-Noriega, Gaby (2008)
The present research studied the relationship between the use of metacognitive strategies, academic motivation and academic achievement in university students. The sample was composed by 116 first semester students, of a private university in Lima Metropolitana. The Scale for Academic Motivation was created to asses the motivational dimensions of: Academic Self-efficacy, Causal Attributions and Achievement Oriented Actions. Positive correlations between metacognitive strategies and academic achievement were found, although results were not predictive. Instead, academic motivation was found to predict achievement in 12,6%.